PELATIHAN PUBLIC SPEAKING MELALUI MESATUA PADA ANAK USIA DINI - Bradah, Bombang Sewu Ramon; Wiguna, Ida Bagus Alit; Sukendri, Nengah (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Public Speaking skills must be learned by children at an early age. This skill needs to be taught to children to help them be brave enough to communicate with people. This research activity aims to train children to have Public Speaking skills through mesatua, where this ability will certainly be useful for life at home and at school and work in the future. The purpose of this research was conducted to add Public Speaking skills through mesatua to early childhood. The method used in this research is descriptive qualitative using observation techniques, and documentation. The results of this study are that children are able and brave to come forward to tell stories well and confidently and become brave to speak in front of their friends. In addition, this activity brings benefits to them, namely increasing confidence in meeting and communicating with many people, adding insight into the history of Hinduism and increasing and preserving mesatua culture.